Novos processos logísticos decorrentes de profundas transformações físicas e funcionais: o caso da Natura Cosméticos - Brasil - Ribeiro, Flavia Martinez (2000)
Considering the physical and functional transfonnations which Natura Cosméticos S.A. has gone through, this study has the purpose of analysing possible advantages arisen from strategic logistics changes. The interviews and observations which took place in the units of the organization, were meaningful and relevant in order to understand the working processes, and transfonnations by which Natura passed through. As a result, it was possible to show some advantages arisen from the implementation of new logistics processes.